An MF alpha 1-SUC2 (alpha-factor-invertase) gene fusion for study of protein localization and gene expression in yeast. - Emr, S D (1983)
The peptide mating pheromone alpha-factor and the hydrolytic enzyme invertase (beta-D-fructofuranoside fructohydrolase, EC 3.2.1.26) are processed from larger precursor proteins during their secretion from yeast cells (Saccharomyces cerevisiae). An in-frame fusion of the structural genes for these two proteins was constructed by connecting the 5'-flanking region and prepro-leader portion of the coding sequence of the alpha-factor gene (MF alpha 1) to a large fragment of the invertase gene (SUC2) lacking its 5'-flanking region and the coding information for the first four amino acids of its signal sequence. Sites that have been implicated in normal proteolytic processing of the alpha-factor precursor have been retained in this construction. The chimeric gene directs synthesis of a high level of active invertase that is secreted efficiently into the periplasmic space, permitting cell growth on sucrose-containing media. This extracellular invertase appears to contain no prepro-alpha-factor sequences. The initial intracellular product is, however, a hybrid protein that can be detected either by treatment of the cells with the drug tunicamycin or by blockage of secretion in a temperature-conditional secretion-defective mutant (sec18). Therefore, prior to its efficient proteolytic removal, the alpha-factor portion of the hybrid protein apparently provides the necessary information for efficient export of the substantially larger protein invertase. Similar to MF alpha 1, the MF alpha 1-SUC2 fusion is expressed in alpha haploids at levels 65-75 times higher than in a haploids or in a/alpha diploids; also, high-level expression is eliminated in mat alpha 1 mutants but not in mat alpha 2 mutants. Unlike expression of SUC2, expression of the fusion is not affected by glucose concentration. Hence, the 5'-flanking region present in the fusion (about 950 base pairs) is sufficient to confer alpha cell-specific expression to the hybrid gene.